2013
DOI: 10.1017/s0007114512006174
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise whey protein hydrolysate supplementation induces a greater increase in muscle protein synthesis than its constituent amino acid content

Abstract: It is well known that ingestion of a protein source is effective in stimulating muscle protein synthesis after exercise. In addition, there are numerous reports on the impact of leucine and leucine-rich whey protein on muscle protein synthesis and mammalian target of rapamycin (mTOR) signalling. However, there is only limited information on the effects of whey protein hydrolysates (WPH) on muscle protein synthesis and mTOR signalling. The aim of the present study was to compare the effects of WPH and amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
0
34
0
1
Order By: Relevance
“…After exercise, the supplement containing wheybased protein promotes a significant increase in the fractional rate of protein synthesis and phosphorylation of the mammalian target of rapamycin (mTOR) levels. Higher amino acid utilization in muscular protein synthesis determinates a lower amino acid hepatic metabolization (Kanda et al 2013). This physiologic mechanism suggests that WP supplementation when associated with RT does not promote hepatic overload.…”
Section: Discussionmentioning
confidence: 99%
“…After exercise, the supplement containing wheybased protein promotes a significant increase in the fractional rate of protein synthesis and phosphorylation of the mammalian target of rapamycin (mTOR) levels. Higher amino acid utilization in muscular protein synthesis determinates a lower amino acid hepatic metabolization (Kanda et al 2013). This physiologic mechanism suggests that WP supplementation when associated with RT does not promote hepatic overload.…”
Section: Discussionmentioning
confidence: 99%
“…The total amount of BCAAs was at 194.2 and 199.6 mg/g in vanilla and chocolate type. In high quality whey protein, the content of BCAAs was reported around at 209 mg/g [27]. The obtained data seemed to match with the nutritional value since such two sports nutritional supplements were made from whey protein.…”
Section: Resultsmentioning
confidence: 76%
“…These results suggest that casein peptide supplementation is effective even in small quantities combined with exercise. Additionally, a previous study demonstrated that post-exercise whey protein hydrolysate supplementation increased muscle protein synthesis compared with ingestion of its constituent amino acids in a rat model 18) . Therefore, it was suggested that the peptide (protein hydrolysate) has bioactive functions, and that peptide ingestion might be more effective than amino acid supplementation.…”
Section: Conflict Of Interestsmentioning
confidence: 95%